Letter from Tom Mboya, 1956 (1956)
1956 1945-1960 "Letter from Tom Mboya, 1956" [T0459.jpg], 1956 Tom Mboya (1930-1969) was one of the most charismatic and articulate trade union leaders in Africa in the 1950s, and a key player in Kenya's independence struggles. During the repression of trade unions following the 1952 Emergency, he was imprisoned, but went on to found the Kenya Labour Workers Union and its Secretary General until 1963. In 1958 after a year studying at Oxford, he returned to be elected [as one of 8 Africans] to the Legislative Council. He led the Kenyan delegation to the 1960 Lancaster House Conference and subsequently led the newly established Kenya African National Union, campaigning for independence and the release of Mzee Jomo Kenyatta from prison. After Kenyan independence in 1963, Mboya became Minister of Justice and Constitutional Affairs, then Minister of Economic Planning and Development under Kenyatta. He was assassinated 5 July 1969 in Nairobi.